Analysis of Good Amil Governance Based on the Zakat Core Principle at BAZNAS Tasikmalaya - Maspupah, Ima (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Zakat management in Indonesia is experiencing rapid progress. One of the factors that drives the optimization of Zakat management in Indonesia is based on the enormous potential of zakat but which has not yet been realized optimally. One of the problems is that the level of public trust in zakat bodies is still low because zakat management is considered unprofessional because it has not implemented the principles of accountability and transparency. The governance of zakat bodies by implementing Good Amil Governance can increase the professionalism of amil so that, The aim of establishing BAZNAS is to maximize the potential of zakat which indirectly has implications for reducing poverty. The aim of this research is to analyze Amil's good governance and also assess Amil's governance based on the Zakat Core Principle at BAZNAS Tasikmalaya. This research uses a qualitative descriptive method with a field research approach. The results of the research show that BAZNAS Tasikmalaya has largely implemented good amil governance, and has carried out good implementation of zakat core principles regarding amil governance in this institution